(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2016)
The levirate marriage is known in Hebrew law and even mentioned in the Old Testament. A prerequisite for the occurrence of the levirate marriage is the death of a brother without children, or without heirs, risking the property unit. In order to protect this property, in addition to the assurance of a social position to the widow, his brother, who was an adult during the life of the dead brother, should marry to his sister-in-law. In the literature, it is mentioned for the levirate marriage an Assyrian origin. The purpose of this work is to analyze the provisions of Middle Assyrian Laws that may have some relevance for the treatment of the levirate marriage.